Inhibition of immunoglobulin folding and secretion by dominant negative BiP ATPase mutants. - Hendershot, L (1996)
A group of resident ER proteins have been identified that are proposed to function as molecular chaperones. The best characterized of these is BiP/GRP78, an hsp70 homologue that binds peptides containing hydrophobic residues in vitro and unfolded or unassembled proteins in vivo. However, evidence that mammalian BiP plays a direct role in protein folding remains circumstantial. In this study, we examine how BiP interacts with a particular substrate, immunoglobulin light chain (lambda LC), during its folding. Wild-type hamster BiP and several well-characterized BiP ATPase mutants were used in transient expression experiments. We demonstrate that wild-type lambda LCs showed prolonged association with mutant BiP which inhibited their secretion. Both wild-type and mutant BiP bound only to unfolded and partially folded LCs. The wild-type BiP was released from the incompletely folded LCs, allowing them to fold and be secreted, whereas the mutant BiP was not released. As a result, the LCs that were bound to BiP mutants were unable to undergo complete disulfide bond formation and were retained in the ER. Our experiments suggest that LCs undergo both BiP-dependent and BiP-independent folding steps, demonstrating that both ATP binding and hydrolysis activities of BiP are essential for the completion of LC folding in vivo and reveal that BiP must release before disulfide bond formation can occur in that domain.